Impact of the New American Hypertension Guidelines on the Prevalence of Postpartum Hypertension - Smith, Graeme N.; Pudwell, Jessica; Saade, George R. (American Journal of Perinatology, 2019)
Cardiovascular disease (CVD) is the leading cause of death and disability among women, with more than half occurring in individuals with hypertension. New blood pressure criteria for the diagnosis of hypertension from the American College of Cardiology/American Heart Association recognize that there is no specific blood pressure threshold that is associated with vascular disease. We performed a secondary analysis of two published postpartum databases (the Pre-Eclampsia New Emerging Team [PE-NET] cohort and the Maternal Health Clinic [MHC] cohort) to determine the impact of the change in blood pressure criteria on the diagnosis of hypertension. The prevalence of hypertension in women with uncomplicated pregnancies (PE-NET control) was 22% compared with 56.4% in those who have had a pregnancy complicated by preeclampsia (PE, PE-NET patient) and 67.2% in those referred to the MHC due to a pregnancy complicated by any of the hypertensive disorders of pregnancy. It is well established that certain complications in pregnancy can reliably identify women with risk factors for future CVD. Thus, pregnancy and the postpartum afford a new opportunity for cardiovascular risk screening that could lead to lifestyle modification and therapeutic intervention. Applying the new guideline criteria at least doubles the prevalence of women with hypertension postpartum.
Keywords: hypertension; preeclampsia; postpartum; cardiovascular disease